Cellulose II Aerogel‐Based Triboelectric Nanogenerator. (27th May 2020) - Zhang, Lei; Liao, Yang; Wang, Yi‐Cheng; Zhang, Steven; Yang, Weiqing; Pan, Xuejun; Wang, Zhong Lin
Abstract: Cellulose‐based triboelectric nanogenerators (TENGs) have gained increasing attention. In this study, a novel method is demonstrated to synthesize cellulose‐based aerogels and such aerogels are used to fabricate TENGs that can serve as mechanical energy harvesters and self‐powered sensors. The cellulose II aerogel is fabricated via a dissolution–regeneration process in a green inorganic molten salt hydrate solvent (lithium bromide trihydrate), where. The as‐fabricated cellulose II aerogel exhibits an interconnected open‐pore 3D network structure, higher degree of flexibility, high porosity, and a high surface area of 221.3 m 2 g −1 . Given its architectural merits, the cellulose II aerogel‐based TENG presents an excellent mechanical response sensitivity and high electrical output performance. By blending with other natural polysaccharides, i.e., chitosan and alginic acid, electron‐donating and electron‐withdrawing groups are introduced into the composite cellulose II aerogels, which significantly improves the triboelectric performance of the TENG. The cellulose II aerogel‐based TENG is demonstrated to light up light‐emitting diodes, charge commercial capacitors, power a calculator, and monitor human motions. This study demonstrates the facile fabrication of cellulose II aerogel and its application in TENG, which leads to a high‐performance and eco‐friendly energy harvesting and self‐powered system. Abstract : Cellulose II aerogels, with the features of high flexibility, porosity, and surface area, are integrated with triboelectric nanogenerators to yield green, sustainable energy harvesting, and sensing devices. By blending other natural polysaccharides to introduce electron‐donating and electron‐withdrawing groups, the performance of the cellulose II aerogel‐based triboelectric nanogenerators can be significantly improved and used for mechanical energy harvesting and motion monitoring.